DISTINCTIONS BETWEEN UTOPIA, ANTIUTOPIA AND DYSTOPIA - Murotalieva Maftuna Shukurulloyevna (Western European Studies, 2024)
The distinctions between utopia, dystopia, and anti-utopia delves into the nuanced realms of speculative fiction, philosophy, and political theory, illuminating the unique characteristics and implications of each concept. Utopia, derived from Sir Thomas More's eponymous work, represents an idealized society where social harmony, economic prosperity, and political stability culminate in the perfect human condition, often serving as a critique of contemporary society's failings
Keywords: Dystopia; anti-utopia; utopia; characteristics